SS18-SSX fusion protein-induced Wnt/β-catenin signaling is a therapeutic target in synovial sarcoma - Trautmann, Marcel; Sievers, E.; Aretz, S.; Kindler, D.; Michels, S.; Friedrichs, N.; Renner, Marcus; Kirfel, J.; Steiner, S.; Huss, S.; Koch, A.; Penzel, Roland; et al. (Oncogene, 2014)
Synovial sarcoma is a high-grade soft tissue malignancy characterized by a specific reciprocal translocation t(X;18), which leads to the fusion of the SS18 (SYT) gene to one of three SSX genes (SSX1, SSX2 or SSX4). The resulting chimeric SS18-SSX protein is suggested to act as an oncogenic transcriptional regulator. Despite multimodal therapeutic approaches, metastatic disease is often lethal and the development of novel targeted therapeutic strategies is required. Several expression-profiling studies identified distinct gene expression signatures, implying a consistent role of Wnt/β-catenin signaling in synovial sarcoma tumorigenesis. Here we investigate the functional and therapeutic relevance of Wnt/β-catenin pathway activation in vitro and in vivo. Immunohistochemical analyses of nuclear β-catenin and Wnt downstream targets revealed activation of canonical Wnt signaling in a significant subset of 30 primary synovial sarcoma specimens. Functional aspects of Wnt signaling including dependence of Tcf/β-catenin complex activity on the SS18-SSX fusion proteins were analyzed. Efficient SS18-SSX-dependent activation of the Tcf/β-catenin transcriptional complex was confirmed by TOPflash reporter luciferase assays and immunoblotting. In five human synovial sarcoma cell lines, inhibition of the Tcf/β-catenin protein-protein interaction significantly blocked the canonical Wnt/β-catenin signaling cascade, accompanied by the effective downregulation of Wnt targets (AXIN2, CDC25A, c-MYC, DKK1, CyclinD1 and Survivin) and the specific suppression of cell viability associated with the induction of apoptosis. In SYO-1 synovial sarcoma xenografts, administration of small molecule Tcf/β-catenin complex inhibitors significantly reduced tumor growth, associated with diminished AXIN2 protein levels. In summary, SS18-SSX-induced Wnt/β-catenin signaling appears to be of crucial biological importance in synovial sarcoma tumorigenesis and progression, representing a potential molecular target for the development of novel therapeutic strategies.
published online 28 October 2013
Gesehen am 07.07.2020